A coating method for high-nickel layered oxide positive electrode material and sulfide all-solid-state battery
The high-nickel layered oxide positive electrode material is coated through acid-base neutralization reaction, which solves the problems of structural instability and prone to side reactions under high pressure, and achieves higher cycling stability and lithium ion conduction capabilities.
Patent Information
- Application Number
- CN202510016107.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-08
AI Technical Summary
The structure of the high-nickel layered oxide positive electrode material is unstable under high pressure, has poor long cycle stability, and is prone to side reactions with the sulfide solid electrolyte at high pressure, resulting in an increase in interface impedance and a decrease in battery performance.
The high-nickel layered oxide positive electrode material is coated through acid-base neutralization reaction, and high-valent metals, halogen elements and Li elements with high electronegativity are used to improve the structural stability of the positive electrode material, avoid direct contact with the sulfide electrolyte, and inhibit the occurrence of side reactions.
The structural stability and cyclic stability of high-nickel cathode materials are improved, the side reaction between the cathode and the sulfide electrolyte is suppressed, and the conduction capacity of lithium ions and the high-voltage stability of the battery is improved.
Smart Images

Figure CN119786581A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium batteries, and in particular relates to a coating method for a high-nickel layered oxide positive electrode material and a sulfide all-solid-state battery. Background Art
[0002] Sulfide solid electrolytes are one of the most promising commercial routes for all-solid-state lithium batteries. High-nickel layered oxides are commonly used as cathode materials for sulfide all-solid-state lithium batteries due to their high specific capacity. However, there are still technical barriers in practical applications: 1) The structure of high-nickel layered oxides is unstable under high pressure and has poor long-cycle stability; 2) Side reactions between high-nickel layered oxides and sulfide solid electrolytes are prone to occur under high pressure, resulting in a sharp increase in interfacial impedance and a decrease in battery performance.
[0003] The present invention utilizes acid-base neutralization reaction to coat high-nickel layered oxide positive electrode materials. The coated components include three elements: high-valent metals, halogen elements with high electronegativity (F or Cl, Br and I have too low electronegativity and are not suitable as positive electrode coating materials, which will cause battery performance degradation), and Li element. The purpose of coating the former two is to improve the structural stability of the high-nickel layered oxide, and the latter provides a lithium source for the positive electrode material, while avoiding contact between the high-nickel layered oxide and the sulfide electrolyte, inhibiting the occurrence of side reactions, and is beneficial to the long-cycle stability of the sulfide all-solid-state lithium battery. Summary of the invention
[0004] The purpose of the present invention is to provide a coating method for a high-nickel layered oxide positive electrode material and a sulfide all-solid-state battery in view of the problems existing in the prior art.
[0005] The purpose of the present invention can be achieved by the following scheme: In a first aspect, the present invention provides a coating method for a high-nickel layered oxide positive electrode material, comprising the following steps: S1. Dissolving a high-nickel layered oxide positive electrode material, a high-valent metal halide, and an alkaline lithium source in a solvent, mixing them evenly, and then centrifuging and filtering them to obtain a mixed powder; S2. calcining the obtained mixed powder to obtain a high-nickel layered oxide positive electrode material with a coated structure.
[0006] As an embodiment of the present invention, in step S1, the high-nickel layered oxide positive electrode material includes one or more of layered transition metal oxides, lithium-rich manganese-based positive electrode materials, nickel-cobalt-manganese ternary positive electrode materials, and nickel-cobalt-aluminum ternary positive electrode materials.
[0007] The chemical formula of the layered transition metal oxide is LiM1O 2 , M1 includes one or more of Co, Ni, and Mn; The chemical formula of the nickel-cobalt-manganese / nickel-cobalt-aluminum ternary positive electrode material is Li[Ni 1-x-y Co x M2 y ]O 2 , M2 includes one or more of Al and Mn, wherein 0<x≤0.2, wherein 0<y≤0.2.
[0008] The chemical formula of the lithium-rich manganese-based positive electrode material is z[Li 1 / 3 Mn 2 / 3 ]O 2 ·(1-z) LiM3O 2 , M3 includes one or more of Co, Ni, and Mn, wherein 0<z≤0.4; As an embodiment of the present invention, in step S1, the high-valent metal halide includes one or more of hexafluorotitanic acid, fluorozirconic acid, fluorotantalate, fluoroantimonic acid, and chloroiridic acid.
[0009] As an embodiment of the present invention, in step S1, the alkaline lithium source includes one or more of lithium acetate, lithium methanol, lithium ethoxide, etc.
[0010] As an embodiment of the present invention, in step S1, the solvent includes one or more solvents such as methanol, ethanol, and acetone.
[0011] As an embodiment of the present invention, in step S1, the mass ratio of the high-nickel layered oxide positive electrode material, the high-valent metal halide, the alkaline lithium source, and the solvent is (90-100): (1-10): (0.5-20): (100-200).
[0012] As an embodiment of the present invention, in step S1, the mixing method is magnetic stirring or ultrasonic oscillation; the time range is 24-36 hours. The speed of magnetic stirring is 100-500 rpm. The power of ultrasonic oscillation is 20-80kHz.
[0013] During the mixing process, the acidic high-valent metal halide and the alkaline lithium source will undergo an acid-base neutralization reaction. Part of the generated product will be adsorbed on the surface of the positive electrode material particles during the mixing and filtration process, and a nano-scale coating layer will be formed only after calcination.
[0014] As an embodiment of the present invention, in step S2, the calcination temperature range is 300-550°C, and the time range is 2-12 hours. The calcination is carried out in a muffle furnace.
[0015] As an embodiment of the present invention, in step S2, the coating material in the obtained high nickel layered oxide positive electrode material with coating structure is Li 2 O and MX amixture. M is a metal in an acidic high-valent metal halide, X is a halogen element (F or Cl), and a≥2. In step S1 of the present invention, an acidic high-valent metal halide undergoes an acid-base neutralization reaction with an alkaline lithium source, and the product is: LiCO 3 , H 2 O.MX a In step S2, the product after further calcination is Li 2 O and MX a If the coating material is directly mixed with the positive electrode material by ball milling, it is impossible to completely cover the surface of the positive electrode active material at the microscopic level. Instead, it is part of the composite positive electrode material, and it is impossible to avoid direct contact between the positive electrode active material and the sulfide electrolyte, thereby achieving the effect of inhibiting the occurrence of positive electrode side reactions.
[0016] In a second aspect, the present invention also provides a sulfide all-solid-state battery comprising a high-nickel layered oxide positive electrode material having the coating structure.
[0017] The Li obtained by calcining the present invention 2 O has good ion conductivity. MX a MX is generated preferentially during the charge and discharge process. b (a>b>0), which is beneficial to the phase change of the positive electrode active material, resulting in poor structural stability. At the same time, the coating layer avoids the contact between the positive electrode active material and the sulfide electrolyte, and does not affect the transmission of lithium ions.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) Sulfide solid electrolytes and high-nickel positive electrode active materials have serious interface side reactions, and high-nickel positive electrode active materials have poor high-voltage stability. The present invention uses halogen elements with high electronegativity, which have stable performance when in contact with sulfide electrolytes; surface coating of high-valent metals on high-nickel positive electrode active materials is beneficial to their structural stability. At the same time, the coating of high-nickel positive electrode active materials with halogen elements with high electronegativity will not reduce the conductivity of lithium ions.
[0019] (2) The present invention utilizes acid-base neutralization reaction to provide lithium source and coats high-valent metals and halogen elements with high electronegativity, which can improve the conductivity of lithium ions while improving the high-voltage stability of the composite positive electrode and inhibiting the side reaction between the active material and the sulfide electrolyte.
[0020] (3) The coating layer of the present invention inhibits the interface side reaction of the composite positive electrode, stabilizes the structural stability of the high-nickel positive electrode active material, and effectively improves the lithium ion conductivity of the composite positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 Comparison of the high nickel layered oxide positive electrode material prepared in Example 1 before and after coating; wherein a is the positive electrode material before coating (scale bar 20 μm), b is the positive electrode material after coating (scale bar 20 μm), and c is the coating layer of the positive electrode material after coating (scale bar 20 nm); Figure 2 The charge-discharge comparison curves of the 1st and 100th cycles of Example 1 and Comparative Example 1 are shown; Figure 3 This is a comparison diagram of the charge and discharge curves of the sulfide solid-state battery prepared in Example 2 and Comparative Example 2 at the 1st cycle and the 500th cycle at a rate of 0.5C; Figure 4 It is the charge and discharge curve of the first cycle of the comparative example; wherein a is the charge and discharge curve of the first cycle of comparative examples 3 to 7, and b is the local enlarged curve in a; Figure 5 This is the element distribution diagram of the positive electrode material obtained in Example 4. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0023] Example 1 1) Weigh 100gLi[Ni 0.80 Co 0.1 M 0.1 ]O 2 1 g of hexafluorotitanic acid and 10 g of lithium ethoxide were dissolved in 100 g of anhydrous ethanol, and ultrasonically vibrated for 24 h until the solution was uniformly mixed. The above solution was centrifuged and filtered to obtain a black powder, which was calcined in a muffle furnace at 500 ° C for 5 h to obtain a coated positive electrode active material; Figure 1 This is a comparison of the high-nickel layered oxide positive electrode material prepared in Example 1 before and after coating, wherein a is the positive electrode material before coating, b is the positive electrode material after coating, and c is the coating layer of the positive electrode material after coating.
[0024] 2) Preparation of composite positive electrode: In a glove box filled with argon, weigh 75 mg of the above-coated positive electrode active material, 22 mg Li 5.5 PS 4.5 Cl 1.5The electrolyte powder and 3 mg VGCF powder were placed in a mortar and ground for 30 min until the powders were evenly mixed and set aside.
[0025] 3) Assemble the pressure cell: In a glove box filled with argon, weigh 40 mg of Li 5.5 PS 4.5 Cl 1.5 The electrolyte powder was placed in a pressure battery mold with a diameter of 10 mm, and the electrolyte powder was rotated and flattened by rotating the stainless steel column, and pressed into tablets on a tablet press at a pressure of 120 MPa for 2 min. 40 mg of the Li 5.5 PS 4.5 Cl 1.5 The surface of the electrolyte sheet was flattened and pressed into a sheet on a sheet press at a pressure of 360 MPa for 2 min. A 10 mm diameter Al foil was placed on the surface of the composite positive electrode sheet as the positive electrode current collector. 5.5 PS 4.5 Cl 1.5 A Si negative electrode is placed on the other side of the electrolyte sheet, and the current collector is Cu foil. After assembly, a pressure of 50 MPa is applied to obtain a sulfide all-solid-state lithium-ion battery.
[0026] Example 2 Weigh 90gLi 1.15 Mn 0.53 Ni 0.265 Co 0.055 O 2 , 2 g of chloroiridic acid and 4 g of lithium methoxide are dissolved in 100 g of anhydrous ethanol, and magnetically stirred for 24 h until the solution is uniformly mixed. The above solution is centrifuged and filtered to obtain a black powder, which is placed in a muffle furnace and calcined at 400° C. for 5 h to obtain a coated positive electrode active material; the remaining steps are the same as in Example 1.
[0027] Example 3 Weigh 95gLiCoO 2 , 10 g of fluorotantalate and 4 g of lithium methoxide are dissolved in 100 g of anhydrous methanol, and ultrasonically shaken for 24 h until the solution is evenly mixed. The above solution is centrifuged and filtered to obtain a black powder, which is placed in a muffle furnace and calcined at 550° C. for 5 h to obtain a coated positive electrode active material; the remaining steps are the same as in Example 1.
[0028] Example 4 Weigh 90gLi 1.15 Mn 0.53 Ni 0.265 Co 0.055 O 2, 10g of fluorozirconic acid and 4g of lithium methoxide were dissolved in 100g of anhydrous methanol, and ultrasonically vibrated for 24h until the solution was uniformly mixed. The above solution was centrifuged and filtered to obtain a black powder, which was placed in a muffle furnace and calcined at 550°C for 5h to obtain a coated positive electrode active material; the remaining steps were the same as in Example 1. The element distribution of the obtained positive electrode material is as follows Figure 5 shown.
[0029] Comparative Example 1 The difference from Example 1 is that the positive electrode active material in the composite positive electrode is uncoated Li[Ni 0.80 Co 0.1 M 0.1 ]O 2 .
[0030] Comparative Example 2 The difference from Example 2 is that the positive electrode active material in the composite positive electrode is uncoated Li 1.15 Mn 0.53 Ni 0.265 Co 0.055 O 2 .
[0031] Comparative Example 3 The difference from Example 3 is that the positive electrode active material in the composite positive electrode is uncoated LiCoO 2 .
[0032] Comparative Example 4 The difference from Example 1 is that hexafluorotitanic acid is replaced by a low-valent metal fluoride: sodium fluoroacetate.
[0033] Comparative Example 5 The difference from Example 1 is that an equal amount of Li 2 O and TiF 4 , and Li[Ni 0.80 Co 0.1 M 0.1 ]O 2 Place them together in anhydrous ethanol for ultrasonic vibration (direct mixing) before proceeding with subsequent operations.
[0034] Comparative Example 6 The difference from Example 1 is that an equal amount of Li 2 O, and Li[Ni 0.80 Co 0.1 M 0.1 ]O 2 Place them together in anhydrous ethanol for ultrasonic vibration before proceeding with subsequent operations.
[0035] Comparative Example 7 The difference from Example 1 is that an equal amount of TiF 4 , and Li[Ni 0.80 Co 0.1 M 0.1 ]O 2 Place them together in anhydrous ethanol for ultrasonic vibration before proceeding with subsequent operations.
[0036] Comparative Example 8 The difference from Example 1 is that an equal amount of Li 2 O and TiF 4 , and the weighed Li[Ni 0.80 Co 0.1 M 0.1 ]O 2 Ball milling was performed (400 rpm, 5 h) to obtain the coated positive electrode active material.
[0037] Performance Testing Figure 2 The following is a comparison of the charge and discharge curves of the sulfide solid-state battery prepared in Example 1 and Comparative Example 1 at 0.1C rate at the 1st and 100th cycles. The discharge capacity of Example 1 at the 1st cycle was 208.20 mAh / g, the first efficiency of the battery was 84.83%, and the capacity decayed to 204.77 mAh / g after 100 charge and discharge cycles, with a capacity retention rate of 98.35%; the discharge capacity of the comparative example at the 1st cycle was 183.79 mAh / g, the first efficiency of the battery was 75.42%, and the capacity decayed to 171.58 mAh / g after 100 charge and discharge cycles, with a capacity retention rate of 93.35%.
[0038] Figure 3 The sulfide solid-state battery prepared in Example 2 and Comparative Example 2 is a comparison of the charge and discharge curves of the first and 500 cycles at a rate of 0.5C. The discharge capacity of the first cycle of Example 2 is 180.22 mAh / g, and the capacity decays to 165.08 mAh / g after 500 charge and discharge cycles, with a capacity retention rate of 91.60%; the discharge capacity of the first cycle of Comparative Example 2 is 175.05 mAh / g, and the capacity decays to 154.97 mAh / g after 500 charge and discharge cycles, with a capacity retention rate of 88.52%.
[0039] Figure 4 It is the first cycle charge and discharge curve diagram of the comparative example; among them, a is the first cycle charge and discharge curve of comparative examples 3 to 7, and b is the local enlarged curve in a.
[0040] Table 1 shows the first cycle charge and discharge data of Example 1 and Comparative Examples 3-7.
[0041] Table 1 Comparison of first cycle charge and discharge (0.1C) data of the embodiment and the comparative example
[0042] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A coating method for a high-nickel layered oxide positive electrode material, characterized in that: The steps include: S1. Dissolving a high-nickel layered oxide positive electrode material, a high-valent metal halide, and an alkaline lithium source in a solvent, mixing them evenly, and then centrifuging and filtering them to obtain a mixed powder; S2. calcining the obtained mixed powder to obtain a high-nickel layered oxide positive electrode material with a coated structure.
2. The coating method according to claim 1, characterized in that: In step S1, the high-nickel layered oxide positive electrode material includes one or more of layered transition metal oxides, lithium-rich manganese-based positive electrode materials, and nickel-cobalt-manganese / nickel-cobalt-aluminum ternary positive electrode materials.
3. The coating method according to claim 2, characterized in that: The layered transition metal oxide comprises one of the following materials: (1) a transition metal oxide having the chemical formula LiM1O2, wherein M1 comprises one or more of Co, Ni and Mn; (2) Nickel-cobalt-manganese / nickel-cobalt-aluminum ternary positive electrode material, whose chemical formula is Li[Ni 1-x-y Co x M2 y ]O2, M2 includes one or more of Al and Mn, wherein 0<x≤0.2, wherein 0<y≤0.2; (3) Lithium-rich manganese-based positive electrode material, whose chemical formula is z[Li 1 / 3 Mn 2 / 3 ]O2·(1-z) Li M3O2, M3 includes one or more of Co, Ni, and Mn, wherein 0<z≤0.
4.
4. The coating method according to claim 1, characterized in that: In step S1, the high-valent metal halide includes one or more of hexafluorotitanic acid, fluorozirconic acid, fluorotantalic acid, fluoroantimonic acid, cobalt fluoride, chloroiridic acid, ruthenium trichloride, tantalum pentachloride, titanium pentachloride, niobium fluoride, ruthenium fluoride, and tantalum fluoride.
5. The coating method according to claim 1, characterized in that: In step S1, the alkaline lithium source includes one or more of lithium acetate, lithium methanol, and lithium ethoxide.
6. The coating method according to claim 1, characterized in that: In step S1, the solvent includes one or more of methanol, ethanol, and acetone.
7. The coating method according to claim 1, characterized in that: In step S1, the mass ratio of the high-nickel layered oxide positive electrode material, the high-valent metal halide, and the alkaline lithium source is (90-100): (1-10): (0.5-20).
8. The coating method according to claim 1, characterized in that: In step S1, the mixing is carried out by magnetic stirring or ultrasonic shaking for 24-36 hours.
9. The coating method according to claim 1, characterized in that: In step S2, the calcination temperature range is 300-550°C, and the calcination time range is 2-12h.
10. A sulfide all-solid-state battery comprising a high-nickel layered oxide positive electrode material with a coating structure obtained by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Lithium-rich manganese-based positive electrode material, preparation method thereof and electrochemical device
CN120978052A
High-nickel positive electrode material for solid-state battery, preparation method of high-nickel positive electrode material and solid-state battery
CN121726389A
High-nickel positive electrode material, preparation method thereof and solid-state battery
CN121983553A